G260 Identification of the health burden for street children and service provision available in kisumu, kenya through focus group discussions and semi-structured interviews. (12th March 2018) - Eder, B
Abstract : Aims: The numbers of children living 'on' or 'of' the street, Street Children and Youth (SCY), could be as high as 150 million. SCY are a particularly vulnerable and under-researched group who face unique challenges. This research uses qualitative methodology to build on current research with SCY In Kenya. It aimed to provide an opportunity for these children to share their experiences and make recommendations for how their health may be improved. Methods: Males aged between 10 and 19 accessing Hope for Victoria Children, HOVIC's (a non-governmental organisation (NGO) working in Kisumu, Kenya) night shelter or 'drop in' programme were eligible for inclusion. Children were invited to take part through a 'Baraza', a traditional community meeting and their Comprehension of Assent given in Swahili. Focus group discussions (FGDs) and semi-structured interviews were conducted, using a Guide of Thematic Topics, transcribed verbatim and thematic analysis carried out. Ethical approval was given by the University of Bristol Health Sciences Ethics Committee. Approval was given from HOVIC and Child.org (the respective NGO partners) and the District Children's Officer for Kisumu County. Results: A total of 37 SCY, all male, aged between 10 and 17 were invited to take part, including 'shelter' and 'drop-in' boys. Three FGDs and six semi-structured interviews with boys as well as four interviews with HOVIC staff were conducted. A total of five key themes were identified. What makes street children vulnerable included the reasons children came to the street, the physical environment and abuse. Substance use, mental health, sexual and reproductive health, unintentional injuries and violence made up The Health Burden of SCY. Health Services were concentrated at shelter's, similar to and including HOVIC and hospitals. Barriers to Healthcare included cost and discrimination. Suggestions were made around Improving the Health of Street Children through centres, hospitals and Government implementation of policy. Conclusion: The experiences, stories and feelings shared by SCY highlighted the key challenges they face on a daily basis. By lending a voice to SCY, we hope this research will make a valuable contribution in implementing policy that meets the needs of this vulnerable population.